PERCEPTIONS AND REACTIONS OF AHMADIYYA TO FATWA INDONESIAN ULAMA COUNCIL (MUI): AN ANTROPHOLOGICAL LINGUSITICS APPROACH - Alnizar, Fariz; Ma?ruf, Amir; Manshur, Fadlil Munawwar (Center for Research and Development of Religious Literature and Heritage, 2019)
Over the past two decades, the trend of fatwa requests has increased. Fatwas issued by certain individuals or organizations are used as references in daily life. Likewise in Indonesia through the Indonesian Ulama Council (MUI) where the desire for asking fatwas is almost the same as the desire for implementing the fatwa itself. Including fatwas related to religious sects such as Ahmadiyya which are often become victims of discrimination and assault. Studies of this research focuses on texts fatwa issued by MUI on Ahmadiyya sect in 1980 and 2005. This study departs from the claims of some researchers who think that the fatwa had a strong correlation with actions and violent behavior that befell the Ahmadiyya Community. Use an anthropological linguistic approach, this study show Jemaah Ahmadiyya considers that fatwas are opinion. As usual opinion, he must be respected. Disagreement with an opinion is common. Because opinions are not binding. Such a pedestal of thinking simultaneously raises attitudes and responses that tend to appear to 'accept what we are'. However, if examined more closely, there are a number of efforts which although they are 'sporadic' and are not interpreted as a specific strategy to counter the actual heretical labelling efforts carried out by the Jemaah Ahmadiyya.